Effects of judicial exclusion of a partner in a joint liability company - Cherifi, Ouiza (Journal of Human Sciences, 2022)
The partner’s right to remain in the company for its life time is one of the right protected by the Algerian lawmaker, especially in the partnership, because this type of company does not allow the partners to leave the company after his training. However, there is an exception, since the lawmaker give the right to exclude any partner from the company through the courts, but this right must comply with a set of provisions and conditions. And if some companies are not affected by the exclusion of one of the partners, it is not the same for the partnership being mainly based on the principle of intuitu personae.